ACADEMIC TRAINING IN THE ADMINISTRATION COURSE: Between Professional Preparation and Entrepreneurial Formation (REMUNOM, 2025)
The research focuses on analyzing the curriculum structure and the graduate profile in the Administration course, emphasizing the alignment between the education provided and students' expectations. The objective of this study is to identify gaps and opportunities for improvement in the curriculum by evaluating students' perceptions of the logic of disciplines, content relevance, and skill development. The methodology used was mixed, combining questionnaires with a Likert scale for quantitative data collection and cross-analysis with theoretical references for qualitative interpretation. The guiding research question was: does the Administration course curriculum meet students' expectations and labor market demands? The findings revealed discrepancies between the traditional education offered and the need for innovative and entrepreneurial content, along with an appreciation of aspects such as practical applicability and faculty expertise. This research aims to provide insights for curriculum adjustments to better align the training of administrators with contemporary demands.